Learning, socialization and education in the digital classroom - Timo Bautz (Education in the North, 2022)
This feature explores what consequences an increased use of tablets and learning software has for teaching, learning and socialization of pupils in classrooms. It is closely oriented to Luhmann´s distinction between social and mental systems and his concept of socialization as a necessary side effect of education (“expectations of expectations”). Concepts central to the theory and the distinction between education and instruction are explained in detail. Finally, these concepts are used to analyze the consequences of classroom-based teaching increasingly relying on individual work with digital media instead of personal interactions among pupils and teachers.